Socioeconomic, Genetic, and Dietary Risk Factors of Ischemic Heart Disease in Pakistan. A Multicenter Case-Control Study - Aamir Siddique, Shoaib Ahmed Zia, Zeeshan Ghous, Salma Kadir, Shameem Bhatti, Muhammad Bilal Moeen-Ud-Din (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ischemic heart disease (IHD) is a leading cause of mortality in the world and has an overt contribution in low- and middle-income countries such as Pakistan. Traditional risk factors (hypertension, diabetes, dyslipidemia) are well known; however, the socioeconomic, dietary, and genetic determinants have not been fully explored. Aims and Objectives: This study aimed to investigate the association between socioeconomic factors, dietary habits, and genetic predisposition in the development of IHD risk in Pakistan. It was specifically designed to find out if adverse socioeconomic conditions, unfavourable dietary patterns, and the presence of the APOE ε4 allele, on their own or in combination, would independently and individually increase the likelihood of IHD. Methods: A Multicenter Case Control Study was conducted on n=250 participants (130 IHD patients and 130 controls) from the Punjab Institute of Cardiology (Lahore) and Chaudhry Pervaiz Elahi Institute of Cardiology (Wazirabad) from June 2022 to June 2023. Blood pressure, body mass index, lipid profile, and fasting blood glucose were measured, and comprehensive clinical evaluations were performed. Structured questionnaires were used to collect socioeconomic and dietary data, and a validated food frequency questionnaire was used to collect dietary data. Fasting blood samples were used for genomic DNA extraction, and PCR-RFLP analysis was used to genotype the APOE gene. Bivariate and multivariate logistic regression was done to determine independent predictors of IHD. Results: They were older IHD patients who were known to have higher BMI, blood pressure, and adverse lipid profiles. IHD patients had lower income and educational levels, higher saturated fat intake, and lower fruit and vegetable consumption. The IHD group had a significantly higher frequency of the APOE ε4 allele. Conclusion: The multifactorial interplay of clinical, socioeconomic, dietary, and genetic factors promptly in this context plays a pivotal role, and hence, an integrated preventive strategy is warranted. Keywords: ischemic heart disease, socioeconomic factors, dietary habits, APOE ε4, genetic predisposition, Pakistan.